Métodos de inactivación de parásitos presentes en pescados comercializados para consumo humano - Fariña, F.A. (2021)
The prevention and control of parasites are essential tasks in the fishing industry that tend to avoid significant economic problems and health risks. There exists some parasites that have a devastating effect on aquaculture, since they find the ideal place to reproduce in the breeding stations. Consequently, it is necessary to use appropriate inactivation methods on fish to guarantee the quality of the food product, preserve its organoleptic characteristics and avoid the contagion of people by zoonotic parasites. To this end, a bibliographic search was carried out in order to describe the main methods of inactivation of zoonotic fish borne parasites reported in Argentina. Freezing, cooking, salting, marinating, smoking and irradiation are postulated as possible treatments to ensure the safety of various fish products and by-products when they are applied under certain conditions. Regulations on parasites, guides and documents for industry and consumer education constitute fundamental strategies to produce safe food for the population.